Are shariah and non-shariah firms’ capital structure determinants and financial performance related? Evidence from Malaysia - Rehan, Raja; Adam Sa'ad, Auwal; Haron, Razali; Hye, Qazi Muhammad Adnan (Asian Economic and Social Society (AESS), 2023)
This comparative analysis is an attempt to explore the core differences among the capital structure determinants of Malaysian Shariah and non-Shariah firms. Besides, this investigation also explores which financial category in Malaysia, either Shariah or non-Shariah, maintained its performance, i.e., earnings; during the peak period of the COVID-19 pandemic and to what extent their performance is related. For analysis purposes, this investigation used 454 firms’ 17 years’ financial data, i.e., 2005-2021. The Panel Data Static models are executed to perform the empirical investigation. The debt-to-equity ratio is selected as a dependent variable, whereas total assets, sales, current assets, growth, return on equity, non-debt tax shield, and earnings per share are nominated as independent variables. The results indicate that fixed assets and growth are core determinants for both types of firms. This endorses the validity of these two investigated determinants for the whole Malaysian firm. Moreover, current assets, non-debt tax shield, fixed assets, growth, and earnings per share are also observed as main and significant determinants for Shariah-tagged firms. The positive significance of tangibility, non-debt tax shield, and liquidity explain why the Trade-off theory is more dominant in the Malaysian context. Besides, the outcomes obtained from descriptive statistics and Independent Two-sample t Test explain that both financial categories of Malaysian listed firms maintained negative earnings during the COVID- 19 peak period, i.e., 2020. The results will help policymakers devise the best financing model i.e., Shariah and non-Shariah, specifically during the uncertain financial fiascos.